Applied Clinical Informatics Journal: A Brief History - Lehmann, Christoph U.; Ball, Marion J.; Haux, Reinhold; Lehmann, Jenna S. (Applied Clinical Informatics, 2022)
In 2009, Schattauer Verlag in Stuttgart, Germany first published the Applied Clinical Informatics (ACI) Journal. ACI has served since its inception as an official journal of the International Medical Informatics Association. Later, the American Medical Informatics Association and the European Federation for Medical Informatics named ACI as an official journal. This manuscript describes the history of the journal from its inception to present day including publication measures, challenges, and successes.
Keywords: Applied Clinical Informatics; publishing; scholarly communication; clinical informatics; workforce; implementation; electronic health record